Current Approaches to Alkyl Levulinates via Efficient Valorization of Biomass Derivatives - Liu, Xiaofang; Yang, Wenjia; Zhang, Qiuyun; Li, Can; Wu, Hongguo (Frontiers in Chemistry, 2020)
Biomass as the non-food, abundant, and carbon-neutral potential resource is alternative to fossil fuel in sustainable preparation of various platform chemicals. Alkyl levulinates (ALs) have found widespread applications in flavoring, plasticizing agents, and fuel additives, and as precursors for building blocks. Several processes have been investigated for the transformation of biomass and its derivatives into ALs, which were mainly achieved by i) direct esterification of levulinic acid (LA) with the corresponding alkyl alcohols, and ii) the alcoholysis reaction carried out on renewable biomass feedstock and derivatives including furfuryl alcohol (FAL), chloromethyl furfural (CMF) and saccharides. This review focuses on illustrating the effect of biomass pretreatment, catalyst texture, possible mechanisms, acidity, and the influence of intermediates for the synthesis of ALs from sustainable resources, which covers a wide range of intermediates, such as diethyl ether (DEE), 4,5,5-triethoxypentan-2-one (TEP), ethoxymethylfuran (EMF), ethyl-D-fructofuranoside (EDFF), and ethyl-D-glucopyranoside (EDGP).